2014
DOI: 10.1108/ilds-01-2014-0010
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking and pondering ASERL interlibrary loan operations, 2010 and 2013

Abstract: Purpose – In 2010 and 2013, the libraries in the Association of Southeastern Research Libraries (ASERL) were surveyed to identify benchmarks and programs to support resource sharing. Benchmarks and challenges identified generate discussions regarding programming, networking, and other support to improve resource sharing operations. This paper seeks to address these issues. Design/methodology/approach – This study compares and contrasts t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Kappus combined data analysis and trend analysis to explain increased borrowing request rates at Gonzaga University (Kappus, 2009). Atkins, et al reported a slight 2% decrease in the average number of total requests between 2010 and 2013 among the Association of Southeastern Research Libraries (Atkins et al, 2014). Through interviews with "thought leaders in resource sharing, " Birch, et al recorded that some institutions were experiencing increases in requests while others experienced decreases (Birch et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kappus combined data analysis and trend analysis to explain increased borrowing request rates at Gonzaga University (Kappus, 2009). Atkins, et al reported a slight 2% decrease in the average number of total requests between 2010 and 2013 among the Association of Southeastern Research Libraries (Atkins et al, 2014). Through interviews with "thought leaders in resource sharing, " Birch, et al recorded that some institutions were experiencing increases in requests while others experienced decreases (Birch et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nearly all respondents continued to provide a campus document delivery service from their own collections, and ArticleExchange experienced a very rapid take up. More such surveys would be very useful (Atkins et al, 2014). A well conducted survey of four major academic Omani libraries found much support for collaboration but identified a number of challenges "such as:…”
Section: Interlending and Document Supplymentioning
confidence: 99%
“…This study aims to map the current resource sharing environment in Canada through the lens of its research libraries in general and the University of Alberta (UA) in particular. Prompted by Mak's (2011) study of resource sharing patterns and trends in Association of Research Libraries (ARL) in the USA during the past 35 years (Mak, 2011), along with more recent benchmarking data from the Association of Southeastern Research Libraries (Atkins et al, 2014), the authors were interested in looking at transactional ILL data from Canada. Connected by more than just a border, did Canadian academic libraries see the same exponential growth in ILL as its neighbour to the south?…”
Section: Introductionmentioning
confidence: 99%